ENT Manifestation of Covid-19: An experience at a tertiary care medical teaching institute of Khyber Pakhtunkhwa - Khurshid Anwar, Adnan Yar Muhammad, Fazal Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of ear, nose and throat related disorders of covid disease in PCR proven positive Covid-19 patients. Methods: This prospective study included 320 Covid-19 positive patients and was conducted at ENT Department of MTI Hayatabad Medical Complex, Peshawar from May 1, 2021 to April 30, 2022. The acute phase of covid-19 was taken as the time interval between the onsets of symptoms as day 1 today 30th post infection. Questions were asked about the following symptoms; flu, sore throat, sinus involvement, taste disturbances, smell disturbances, hoarseness and hearing loss. Clinical examination and relevant investigations were carried out to make a diagnosis. The data was documented on a proforma & analyzed using SPSS 26.0 for windows to determine the frequencies of signs & symptoms related to ENT. Results: A total of 320 patients were included in the study. The ages ranged from 18-50 years with mean age of 33.96 years. The age group 18-25 years mostly presented with symptoms related to ENT. Upper respiratory tract infection was the commonest symptom (60.6%) followed by sore throat (57.5%). Smell and taste disturbances accounted for in 46.3% & 15.3 % of the patients respectively. Fungal rhinosinusitis was observed in 6.9% of the patients. As there is a wide variation of the ENT symptoms in covid disease, it is important to know the predictive symptoms so that appropriate measures can be adopted. Identification & isolation of patients will prevent spread of disease and focused therapy and investigations. Practical implication Conclusion: The portal of entry for the SARS-CoV-2 is through the upper airway. It is important to know the symptoms related to ENT to make an early diagnosis and therefore, institute measures for management and prevention of further spread of the disease. Keywords: Covid-19, Anosmia, Dysosmia, Dysgeusia, Mucormycosis, Sore Throat